LABOR MOBILITY IN THE REPUBLIC OF KAZAKHSTAN - A.M. Tulebayeva,; Z.A. Salzhanova, (Academic Journal of Physical and Chemical Sciences, 2019)
The relevance of this article lies in the fact that the analysis of indicators of labor resources makes it possible to judge the effectiveness of the state policy in the field of employment regulation, which it is illegal to consider outside economic processes, which are objective prerequisites for the realization of opportunities, both of an individual and of the population countries in general. The current situation in the labor market is always in the center of attention of the state, business and society as a whole. It affects both the economic development of the country, social policy, the competitiveness of enterprises, and the welfare of the individual. At the same time, the labor market itself is undergoing the strongest influence from demographic, economic, technological and political trends, which makes it unique in each country. This leads to the need for a comprehensive analysis, both at the global and national levels. The article analyzes the labor market on the basis of official statistical data of the Republic of Kazakhstan, where internal labor migration processes are also actively involved, and where it is necessary to apply measures to increase labor mobility, primarily aimed at encouraging migration from labor-intensive to labor-deficient regions. When writing the article, general scientific methods of cognition (statistical, normative analysis, synthesis, analogy, generalization), empirical-theoretical (collection, study and comparison of data), as well as methods of scientific knowledge (historical, legal, systemic, comparative legal) were used. ). In processing and systematizing the data, grouping and classification methods were used. The information and statistical base of the study was compiled from official periodical and information and analytical publications of the Republic of Kazakhstan.